Meso-Aryl substituted free-base tripyrrins: preparation and electrochemically induced protonation/deprotonation reactions. Single crystal X-ray analysis of (2, 6-diFPh)2TriPyH. Issue 117 (10th November 2015) - Feng, Ru; Ou, Zhongping; Xue, Zhaoli; Fang, Yuanyuan; Song, Yang; Kadish, Karl M.
Abstract : Three meso -substituted free-base tripyrrins were successfully isolated as side-products from the synthesis of triarylcorroles and characterized as to their electrochemical properties in nonaqueous media. Abstract : Three meso -substituted pyrrole-terminated tripyrrins were isolated for the first time as side products in the synthesis of triarylcorroles and characterized by spectroscopic and electrochemical techniques. The examined compounds are represented as (Ar)2 TriPyH, where the TriPy is the conjugated tripyrrin monoanion and Ar a 2, 6-diFPh, 2, 6-diClPh or 2, 4-diClPh substituent. A single crystal X-ray structure of (2, 6-diFPh)2 TriPyH is also presented. This is the first X-ray structure of a meso -aryl substituted tripyrrin. Each tripyrrin undergoes two reductions and three oxidations in CH2 Cl2 . The first one-electron addition and first one-electron abstraction lead to formation of π–anion and π–cation radicals with a potential separation between the two processes of 1.71 to 1.76 V. However, both electrogenerated products are unstable and undergo a rapid chemical reaction to give new electroactive species which are identified as the deprotonated and protonated compounds, respectively. The reaction products were characterized by spectroelectrochemistry and comparisons are made with spectroscopic data obtained during base and acid titrations in CH2 Cl2 .